Undergraduate Students’ Learner Autonomy during Thesis Writing: The Case of a Group of EFL Students in Indonesia - Utami, Artine Ayu; Kuswandono, Paulus (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Learner autonomy has recently gained popularity among scholars of ELT as autonomy is pivotal, especially during the thesis writing process. This study aims to explore undergraduate students’ learner autonomy during thesis writing. A case study method was employed to explore and record students' autonomy. A case study is a comprehensive, all-encompassing description and study of specific phenomena like a program, an institution, a person, a process, or a social unit.  The data were collected from semi-structured interviews, weekly writing progress of five EFL students in Indonesia, and observation in the classroom. As a case study, those five participants were sufficient to represent their learning autonomy demonstrated during the semester. Oxford's taxonomy of learner autonomy was used to find the emerged themes from the interviews. The data raised three themes: motivation, agency, and writing strategies. The extrinsic motivation was more dominant than intrinsic motivation in this study. Moreover, three of five participants indicated highly intense motivation. Regarding learning strategy, students with more motivation were able to explore more writing strategies. It was found that social strategies were widely employed by the participants. They like to discuss with their peers and ask for feedback from their supervisor. Agency during undergraduate thesis writing is still underrepresented, particularly the one demonstrating students’ decisions about their research trajectory. This study revealed that their agency is affected by their experiences and projective dimension to make improvements. Supervisor instructions play a crucial role in the development of students' autonomy. Hence, further investigation in this area is needed. This study offers research and practical implications for future research and educators, especially in higher education. This study provides a future research direction for both students and lecturers to foster learner autonomy during undergraduate thesis writing.Keywords: Agency, Learner Autonomy, Motivation, Writing Strategies